2018
DOI: 10.7189/jogh.08.020414
|View full text |Cite
|
Sign up to set email alerts
|

Seven years of telemedicine in Médecins Sans Frontières demonstrate that offering direct specialist expertise in the frontline brings clinical and educational value

Abstract: BackgroundMédecins Sans Frontières (MSF), a medical humanitarian organization, began using store-and-forward telemedicine in 2010. The aim of the present study was to describe the experience of developing a telemedicine service in low-resource settings.MethodsWe studied the MSF telemedicine service during the period from 1st July 2010 until 30th June 2017. There were three consecutive phases in the development of the service, which we compared. We also examined the results of a quality assurance program which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
(29 reference statements)
2
43
0
Order By: Relevance
“…It also suggests that for many of the cases, co-operation with other rare disease ERNs would be beneficial for patients, as this would allow experts from several different disciplines to comment on the same cases. Also, a similar tendency to increasing complexity of queries over time has been observed previously in other telemedicine approaches [17].…”
Section: Discussionsupporting
confidence: 81%
“…It also suggests that for many of the cases, co-operation with other rare disease ERNs would be beneficial for patients, as this would allow experts from several different disciplines to comment on the same cases. Also, a similar tendency to increasing complexity of queries over time has been observed previously in other telemedicine approaches [17].…”
Section: Discussionsupporting
confidence: 81%
“…At the time of our 2015 review, most studies reported high PCP satisfaction with e-consults, including perceived value, improved timeliness of specialty input, and enhanced communication with specialist. Newer studies using PCP surveys support these findings, 11,13,14,[18][19][20][21][22]24,26,[29][30][31][33][34][35][36]41,54,57,60,[62][63][64][65][67][68][69][70][71] and 2 qualitative studies also report generally high PCP satisfaction. 7,39 More recent studies have also described a strong educational benefit to less-experienced PCPs.…”
Section: Patient and Clinician Experiencementioning
confidence: 85%
“…Since 2015, articles have been published that extend e-consult to patients that might not have had access to a specialist face-to-face visit in the first place, such as patients with rare conditions 46 and patients in rural, 42 extremely remote, 27 or otherwise low-resource regions. 68 Faster access to specialist input compared to face-to-face visits. Sleep medicine e-consultation followed by the specialists' order of a sleep study and positive airway pressure therapy, if indicated, resulted in a decrease over 4 years in the interval between sleep consult and positive airway pressure prescription from 60 days to 7 days.…”
Section: Access To Carementioning
confidence: 99%
“…Although a few reports [13,14] have indicated that telemedicine is more cost-effective than face-toface medical care, due to recent advances in information and communication technology (ICT), the results of the current study support the most basic principle [15]-direct patient education is the most effective method of managing chronic diseases.…”
Section: Discussionmentioning
confidence: 71%